Resin composition and molding thereof
Patent Information
- Application Number
- JP2024110222
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-06
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-20
AI Technical Summary
【0010】 本発明によれば、初期の伸びに優れる成形体が得られるポリブテン樹脂組成物、および初期の伸びに優れる成形体を提供できる。
Smart Images

Figure 2025024679000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article thereof. [Background technology]
[0002] Molded articles of polybutene resin are used for hot and cold water supply piping etc. because of their excellent heat resistance, mechanical strength, flexibility, light weight etc. It is known that the crystallization of polybutene resin progresses over time after molding in molded articles of polybutene resin (Patent Document 1).
[0003] On the other hand, it is known that cyclodextrin and cyclodextrin clathrates exhibit a nucleating effect for polyolefin resins, etc. Patent Document 2 and Non-Patent Document 1 show that the addition of a cyclodextrin clathrate increases the heat of crystal fusion and the heat of crystallization, and promotes crystallization. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5902991 [Patent Document 2] Patent No. 5077846 [Non-patent literature]
[0005] [Non-Patent Document 1] Saito et al., Polymer Journal, Vol. 68, No. 6, pp. 353-369 (2011) Summary of the Invention [Problem to be solved by the invention]
[0006] Since cold and hot water supply piping is used in an environment where it is exposed to high-temperature water for a long period of time, it is required to have durability capable of withstanding long-term use. The mechanical strength of molded polybutene resin improves over time as the polybutene resin crystallizes, but as the proportion of non-crystalline parts decreases, the flexibility (elongation) decreases and the impact strength and long-term pressure resistance decrease.
[0007] If the initial elongation percentage after production of the molded article is high, the elongation percentage after aging will also be high. Therefore, in order to ensure flexibility after aging and improve long-term durability, it is considered effective to increase the initial elongation percentage. Therefore, an object of the present invention is to provide a polybutene resin composition which can give a molded article having excellent initial elongation, and to provide a molded article having excellent initial elongation. [Means for solving the problem]
[0008] As a result of extensive research, the present inventors have found that the addition of a specific additive to a polybutene resin retards the crystallization of the polybutene resin and increases the initial elongation of the molded article. Incidentally, Patent Document 2 and Non-Patent Document 1 show that the addition of a cyclodextrin inclusion compound promotes crystallization, but do not show that crystallization is delayed (the proportion of non-crystalline portions increases).
[0009] The present invention is based on these findings and has the following aspects. [1] A composition comprising a polybutene resin and an additive, The heat of crystalline fusion in the range of 60°C to 140°C measured by a differential scanning calorimeter is 37.0 mJ / mg or less; Resin composition. [2] The resin composition according to [1], wherein the additive contains at least one selected from the group consisting of methylcyclodextrin and an inclusion compound containing methylcyclodextrin and polypropylene wax. [3] The resin composition according to [2], wherein the content of the methyl cyclodextrin is 0.2 to 5.0 mass %. [4] The resin composition according to [2], wherein the content of the inclusion compound is 0.2 to 5.0 mass %. [5] A molded article comprising the resin composition according to any one of [1] to [4]. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polybutene resin composition which can give a molded article having excellent initial elongation, and a molded article having excellent initial elongation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present invention will be described. The following embodiments are merely examples for explaining the present invention, and are not intended to limit the present invention to these embodiments. In this specification, "cyclodextrin" is also referred to as "CD." "Differential scanning calorimetry" is also referred to as "DSC." In this specification, the use of "to" indicating a range of values means that the values before and after it are included as the lower limit and upper limit.
[0012] The resin composition according to one embodiment of the present invention contains a polybutene resin and an additive. Each component will be described in detail later.
[0013] The resin composition of the present embodiment has a crystalline fusion heat (hereinafter also referred to as "ΔH") of 37.0 mJ / mg or less in the range of 60°C to 140°C measured by DSC. When ΔH is 37.0 mJ / mg or less, crystallization of the polybutene resin after molding of the resin composition is delayed, and the initial elongation of the molded article is improved. In addition, the warm water resistance and long-term creep performance are also improved. ΔH is preferably 35.0 mJ / mg or less. From the viewpoint of ensuring the strength of the molded article, ΔH is preferably 30.0 mJ / mg or more, more preferably 33.0 mJ / mg or more. Details of the method for measuring ΔH are as described in the Examples below. ΔH can be adjusted by the type and content of the additive.
[0014] The resin composition of the present embodiment preferably has a crystallization temperature (hereinafter also referred to as "Tc") measured by DSC of 70.0 to 86.0°C, more preferably 75.0 to 86.0°C. When Tc is equal to or greater than the lower limit, crystallization after production of a molded product is rapid, improving productivity. When Tc is equal to or less than the upper limit, the proportion of amorphous portions increases, improving the flexibility of the resin. Details of the method for measuring Tc are as described in the Examples below. Tc can be adjusted by the type and content of additives.
[0015] The resin composition of this embodiment is melt-kneaded, molded into a sheet of 1 mm thickness, cooled and solidified, and aged at room temperature (20 to 30°C) for 100 hours. A test piece cut into a dumbbell shape No. 8 as specified in JIS K6251 from the obtained molded body has a tensile elongation measured under conditions of a chuck distance of 30 mm, a temperature of 95°C, and a tensile speed of 12.5 mm / min of preferably 300% or more, more preferably 400% or more. The higher the tensile elongation, the higher the initial flexibility of the molded body of the resin composition and the easier it is to maintain flexibility over a long period of time. The upper limit of the tensile elongation is not particularly limited, but is, for example, 550%. The details of the method for measuring the tensile elongation are as described in the Examples section below.
[0016] <Polybutene resin> Examples of polybutene resins include homopolymers of 1-butene and copolymers of 1-butene and an α-olefin other than 1-butene. The content of structural units based on 1-butene relative to the total of all structural units constituting the polybutene resin is, for example, 80 to 100 mol %.
[0017] Examples of the α-olefin other than 1-butene include ethylene, propylene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, and 1-octene. The number of carbon atoms of the α-olefin other than 1-butene is preferably 3 to 8. The α-olefin other than 1-butene may be used alone or in combination of two or more kinds.
[0018] The melt flow rate (hereinafter, also referred to as "MFR") of the polybutene resin is preferably 0.01 to 10 g / 10 min, more preferably 0.1 to 5 g / 10 min. When the MFR of the polybutene resin is equal to or higher than the lower limit, the molecular weight of the polybutene resin is reduced, improving the flowability and improving the moldability. When the MFR of the polybutene resin is equal to or lower than the upper limit, the long-term durability of the molded article is improved. The MFR of polybutene resin is a value measured in accordance with JIS K7210-1 under conditions of a temperature of 190°C and a load of 2.16 kg.
[0019] The polybutene resin may be a commercially available product or may be produced by a known production method. Examples of the production method of the polybutene resin include a method of one-stage polymerization or multi-stage polymerization of 1-butene alone or 1-butene and an α-olefin other than 1-butene by a known polymerization method using any polymerization catalyst. The polybutene resin may be used alone or in combination of two or more kinds.
[0020] The content of the polybutene resin is preferably 90.0 to 99.5 mass%, more preferably 95.0 to 99.5 mass%, and even more preferably 97.5 to 99.5 mass%, based on the total mass of the resin composition. When the content of the polybutene resin is equal to or more than the lower limit, the strength properties are improved. When the content of the polybutene resin is equal to or more than the lower limit, a sufficient amount of additives can be contained to set ΔH to 37.0 mJ / mg or less.
[0021] <Additives> By including an additive in the resin composition, ΔH can be set to 37.0 mJ / mg or less. Examples of additives include methyl CD and an inclusion compound containing methyl CD and polypropylene wax. By including methyl CD or an inclusion compound containing methyl CD and polypropylene wax, ΔH can be reduced.
[0022] Methyl CDs are CDs modified with methyl groups, in which the hydrogen atoms of at least some of the hydroxyl groups of the CDs are replaced with methyl groups. CD can be exemplified by those having 6 to 8 glucose units bonded together, and specific examples include α-CD with 6 glucose units, β-CD with 7 glucose units, and γ-CD with 8 glucose units. Among them, β-CD is preferred because it is a membered ring that easily incorporates polypropylene wax. That is, methyl-β-CD is preferred as methyl CD. An example of an inclusion compound is a compound in which polypropylene wax is included in methyl CD.
[0023] Examples of the polypropylene wax constituting the inclusion compound include a homopolymer of propylene and a copolymer of propylene and an α-olefin other than propylene. The content of structural units based on propylene relative to the total of all structural units constituting the propylene wax is, for example, 85 to 100 mol %.
[0024] Examples of the α-olefin other than propylene include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, and 1-octene. The number of carbon atoms of the α-olefin other than propylene is preferably 3 to 8. The α-olefin other than propylene may be used alone or in combination of two or more kinds.
[0025] The melt viscosity of the polypropylene wax is preferably 40 to 5000 mPa s, more preferably 60 to 250 mPa s. When the melt viscosity of the polypropylene wax is equal to or higher than the lower limit, the strength properties are improved, whereas when the melt viscosity is equal to or lower than the upper limit, the molecular weight of the polypropylene wax is reduced, making it easier for methyl CD to be included in the polypropylene. The melt viscosity of the polypropylene wax is a value measured using a BL type viscometer at a temperature of 160°C.
[0026] As a method for producing the inclusion compound, for example, methyl CD and polypropylene wax are mixed to form a mixed powder, and the mixed powder is hot-pressed. The methyl CD and polypropylene wax may be commercially available products or may be produced by a known production method. The heating temperature of the hot press is, for example, 150 to 200° C. The heating time of the hot press is, for example, 0.5 to 3 hours. The formation of inclusion compounds is 1 This can be confirmed by the appearance of a peak at a position different from that of methyl CD using H-NMR.
[0027] Either methyl CD or the inclusion compound may be used alone, or both may be used in combination. When both are used in combination, the methyl CD as an additive and the methyl CD constituting the inclusion compound may be the same or different.
[0028] When the additive contains methyl CD, the content of methyl CD is preferably 0.2 to 5.0 mass%, more preferably 0.3 to 3.0 mass%, and even more preferably 0.4 to 2.6 mass%, based on the total mass of the resin composition. When the content of methyl CD is equal to or more than the lower limit, ΔH is easily controlled to 37.0 mJ / mg or less, and when it is equal to or less than the upper limit, strength properties are improved.
[0029] When the additive contains an inclusion compound, the content of the inclusion compound is preferably 0.2 to 5.0 mass%, more preferably 0.3 to 3.0 mass%, and even more preferably 0.4 to 2.6 mass%, based on the total mass of the resin composition. When the content of the inclusion compound is equal to or more than the lower limit, ΔH is easily controlled to 37.0 mJ / mg or less, and when it is equal to or less than the upper limit, strength properties are improved.
[0030] When the additive contains methyl CD and the inclusion compound, the total content of methyl CD and the inclusion compound is preferably 0.2 to 5.0 mass%, more preferably 0.3 to 3.0 mass%, and even more preferably 0.4 to 2.6 mass%, based on the total mass of the resin composition. When the total content of methyl CD and the inclusion compound is equal to or more than the lower limit, ΔH is easily controlled to 37.0 mJ / mg or less, and when it is equal to or less than the upper limit, the strength properties are improved.
[0031] The additive may further contain other additives other than methyl CD and the inclusion compound, as necessary. Examples of other additives include crystal nucleating agents, process heat stabilizers, UV absorbers, organic fillers, inorganic fillers, pigments, dyes, processing aids, α-olefin resins, etc. These other additives may be used alone or in combination of two or more.
[0032] <Method of producing resin composition> The resin composition can be produced by melt-kneading a polybutene resin and an additive. As the melt-kneading method, a known method can be used, for example, a method using an extruder having a screw. The temperature during melt kneading is, for example, 150 to 200°C.
[0033] <Molded body> The resin composition can be molded into a molded article by a known method. The shape of the molded article is appropriately determined depending on the application. When the molded article is used as a pipe for cold water / hot water supply, a floor heating pipe, or the like, the shape of the molded article is a cylindrical or polygonal tubular shape. The size of the molded article is generally determined according to the application it is used in. When the molded article is a pipe, it preferably has an outer diameter of 6 to 200 mm, a thickness of 1 to 30 mm, and a length of 0.3 to 200 m.
[0034] The molded article can be produced by a known method, for example, by plasticizing a resin composition, molding the plasticized resin composition (plasticized product) into a desired shape, and cooling and solidifying it. An example of the plasticization method is a method of heating the resin composition. The heating temperature is, for example, 150 to 200°C. The resin composition may be heated and kneaded at the same time. A known method can be used as the kneading method, and an example of the method is a method using an extruder having a screw. The temperature during kneading is, for example, 150 to 200°C.
[0035] As the molding method, a known method can be used, for example, extrusion molding, injection molding, and compression molding. As the extrusion molding method, a method in which a plasticized material is discharged from a die into an arbitrary shape, the discharged plasticized material is taken up, and then the taken up plasticized material is cooled is exemplified. As the injection molding method, a method in which a plasticized material is injected into a mold having a core and a cavity, the mold is cooled, and a molded body is taken out from the mold is exemplified. As the compression molding method, a method in which a resin composition is placed in a mold cavity, sealed, and heat and pressure are applied to plasticize the resin composition, and then the cavity is cooled is exemplified. The temperature for cooling and solidifying is, for example, -10 to 50°C. After cooling and solidifying, the obtained molded body may be cured. Curing promotes crystallization and can impart strength properties. Curing conditions include, for example, 15 to 40° C. and 24 to 100 hours.
[0036] The molded article may be a multi-layer molded article having at least one coating layer and one reinforcing layer on one side, both sides, or in the middle of the layer of the resin composition. The material of the coating layer is preferably a flexible thermoplastic resin. Examples of such thermoplastic resins include polyolefin, polyvinylidene fluoride, and polyamide. The thermoplastic resin may be a single type or a combination of two or more types. The thickness of the coating layer is preferably 0.01 to 5 mm, and more preferably 0.05 to 0.2 mm. The material of the reinforcing layer is preferably a metal, for example, aluminum or copper, and the thickness of the reinforcing layer is preferably 0.01 to 10 mm, more preferably 0.2 to 5 mm. The multi-layer molded article is produced, for example, by multi-layer extrusion molding.
[0037] According to the resin composition described above, the crystallinity of the polybutene resin can be adjusted by the additive, and by increasing the amorphous content, the initial elongation is improved, and a molded article having excellent long-term durability can be obtained. The molded article of the resin composition also has excellent warm water resistance. EXAMPLES
[0038] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0039] (Measurement method) <Heat of crystal fusion (ΔH)> The ΔH of the resin composition was measured using a DSC (DSC7020 manufactured by Hitachi High-Tech Science Corp.) according to the following procedure. About 5 mg (5 mg ± 0.5 mg) of the sample was heated from 20°C to 210°C at a heating rate of 10°C / min while purging with nitrogen at a flow rate of 50 mL / min, then cooled from 210°C to 20°C at a heating rate of 10°C / min, and after the cooling was completed, the temperature was raised from 20°C to 210°C at a heating rate of 10°C / min, and the ΔH in the range of 60 to 140°C was calculated from the peak area observed at that time.
[0040] <Crystallization temperature (Tc)> The Tc of the resin composition was measured using a DSC (DSC7020 manufactured by Hitachi High-Tech Science Corp.) according to the following procedure: Approximately 5 mg of a sample was heated from 20°C to 210°C at a heating rate of 10°C / min while purging with nitrogen at a flow rate of 50 mL / min, and then cooled from 210°C to 20°C at a heating rate of 10°C / min, and Tc was calculated from the peak temperature observed during the heating.
[0041] <Tensile elongation> The sheet-like molded body obtained in each example was cured (crystallized) for 100 hours at 23°C. Then, a dumbbell-shaped No. 8 specimen as specified in JIS K6251 was cut out from the molded body to prepare a test piece. A tensile test was performed on the obtained test piece in accordance with JIS K7161 using an autograph manufactured by Shimadzu Corporation to determine the tensile elongation. The tensile test was performed at a chuck distance of 30 mm at a temperature of 95°C and a tensile speed of 12.5 mm / min. The higher the tensile elongation, the more flexible the test piece is, and the easier it is to maintain flexibility over the long term. Tensile elongation of 300% or more was evaluated as good (○), and that of less than 300% was evaluated as poor (×).
[0042] <Hot water resistance> To evaluate the warm water resistance, the antioxidant capacity (oxidation induction time) was measured by the following method for the sheet-like molded products obtained in Example 2 and Comparative Example 1. A higher antioxidant capacity (longer oxidation induction time) indicates better warm water resistance. Measurement method for antioxidant capacity: A sheet-shaped molded product was immersed in warm water at 80°C for 10,000 hours. After immersion, the molded product was kept at 190°C in an oxygen atmosphere in a DSC (differential scanning calorimeter) and the time until decomposition heat generation began (oxidation induction time) was measured, and this value was taken as the antioxidant capacity.
[0043] <Long-term creep performance> To evaluate the long-term creep performance, rectangular test pieces 10 mm wide x 80 mm long were cut out from the sheet-like molded products obtained in Example 2 and Comparative Example 1, and the knee point time was evaluated using the following method. A longer knee point, that is, a longer period in the ductile fracture region, indicates better long-term creep performance. Knee point measurement method: A full-perimeter notch tensile creep test was conducted in which a sharp notch was made with a razor blade around the entire center of a rectangular test piece, tensile creep was performed under a constant load, and the time to fracture was measured. The test was conducted in an 80°C surfactant aqueous solution, with various loads being changed, and a series of data (creep diagram) was obtained between stress and fracture time. It is known that the creep diagram of polybutene resin has two regions: a region with a gentle slope indicating ductile fracture on the high stress / short time side, and a region with a steep slope indicating brittle fracture on the low stress / long time side. The turning point from the ductile fracture region to the brittle fracture region is called the knee point. The time to the knee point was calculated from the creep diagram, and this value was used as the long-term creep performance.
[0044] (Raw materials used) PB: Polybutene resin, Mitsui Chemicals' "Viewron (registered trademark) P5050N", MFR (190°C, 2.16 kg) 0.5 g / 10 min, density 0.92 g / cm 3 . PP wax: Polypropylene wax, Sanyo Kasei "Viscol 660-P", melt viscosity (160℃) 70 mPa·s. · CD-M: Methyl-β-CD, manufactured by CycloChem. · CD-HP: Hydroxypropyl-β-CD, manufactured by CycloChem. CD-F: β-CD, manufactured by CycloChem. CD-M / PP: an inclusion compound containing CD-M and PP wax. Produced in Production Example 1 below.
[0045] (Production Example 1) Production of CD-M / PP A mixed powder was prepared by mixing 3 parts by mass of CD-M and 1 part by mass of PP wax. The mixed powder was melted at 180°C for 1 hour using a hot press, and then cooled using a cooling press to obtain CD-M / PP.
[0046] Example 1 99.5 parts by mass of PB and 0.5 parts by mass of CD-M were fed to a Labo Plastomill (manufactured by Toyo Seiki Seisakusho), melted and kneaded to form a plasticized product, which was then pressed in a hot press device and cooled and solidified to obtain a sheet-like molded product with a thickness of 1 mm. The obtained molded product was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1. Separately, a sheet-like molded product having a thickness of 3 mm was obtained in the same manner as above, except that the spacer thickness during pressing was changed. The long-term creep performance of the obtained molded product was measured. The results are shown in Table 1.
[0047] Example 2 A molded article was obtained in the same manner as in Example 1, except that PB was 99 parts by mass and CD-M was 1 part by mass. The molded article was measured for ΔH, Tc, tensile elongation and warm water resistance. The results are shown in Table 1.
[0048] Example 3 A molded article was obtained in the same manner as in Example 1, except that PB was 97.5 parts by mass and CD-M was 2.5 parts by mass. The molded article was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1.
[0049] Example 4 A molded article was obtained in the same manner as in Example 1, except that PB was 98.7 parts by mass and CD-M was 1.3 parts by mass of CD-M / PP. The obtained molded article was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1.
[0050] Comparative Example 1 A molded article was obtained in the same manner as in Example 1, except that CD-M was omitted and PB was used in an amount of 100 parts by mass. The molded article was measured for ΔH, Tc, tensile elongation, and warm water resistance. The results are shown in Table 1. Separately, a sheet-like molded product having a thickness of 3 mm was obtained in the same manner as above, except that the spacer thickness during pressing was changed. The long-term creep performance of the obtained molded product was measured. The results are shown in Table 1.
[0051] Comparative Example 2 A molded article was obtained in the same manner as in Example 1, except that PB was 99.9 parts by mass and CD-M was 0.1 parts by mass. The molded article was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1.
[0052] Comparative Example 3 A molded article was obtained in the same manner as in Example 2, except that CD-HP was used instead of CD-M. The molded article was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1.
[0053] Comparative Example 4 A molded article was obtained in the same manner as in Example 2, except that CD-F was used instead of CD-M. The molded article was measured for ΔH, Tc, and tensile elongation. The results are shown in Table 1.
[0054] [Table 1]
[0055] The molded articles of the resin compositions of Examples 1 to 4 were excellent in tensile elongation. On the other hand, the molded articles of the resin compositions of Comparative Examples 1 to 4, which had a ΔH of more than 37.0 mJ / mg, were poor in tensile elongation. The molded article of the resin composition of Example 2 was superior to Comparative Example 1 in hot water resistance and long-term creep performance.
Claims
1. Contains a polybutene resin and an additive, The heat of crystalline fusion in the range of 60°C to 140°C measured by a differential scanning calorimeter is 37.0 mJ / mg or less; Resin composition.
2. The resin composition according to claim 1, wherein the additive comprises at least one selected from the group consisting of methylcyclodextrin and an inclusion compound containing methylcyclodextrin and polypropylene wax.
3. The resin composition according to claim 2, wherein the content of the methyl cyclodextrin is 0.2 to 5.0 mass%.
4. The resin composition according to claim 2, wherein the content of the inclusion compound is 0.2 to 5.0 mass%.
5. A molded article comprising the resin composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
JP1975077846A
Marine floating structure
JP1984002991A
Cited By
Apparatus for providing tracking data for tire auto mounting
KR102813186B1